Population structure, allelic variation at Rht-B1 and Ppd-A1 loci and its effects on agronomic traits in Argentinian durum wheat - Achilli, Ana Laura; Roncallo, Pablo Federico; Larsen, Adelina Olga; Dreisigacker, Susanne; Echenique, Viviana (Springer, 2022)
Exploring the genetic variability in yield and yield-related traits is essential to continue improving genetic gains. Fifty-nine Argentinian durum wheat cultivars were analyzed for important agronomic traits in three field experiments. The collection was genotyped with 3565 genome-wide SNPs and functional markers in order to determine the allelic variation at Rht-B1 and Ppd-A1 genes. Population structure analyses revealed the presence of three main groups, composed by old, modern and genotypes with European or CIMMYT ancestry. The photoperiod sensitivity Ppd-A1b allele showed higher frequency (75%) than the insensitivity one Ppd-A1a (GS105). The semi-dwarfism Rht-B1b and the Ppd-A1a (GS105) alleles were associated with increases in harvest index and decreases in plant height, grain protein content and earlier heading date, although only the varieties carrying the Rht-B1 variants showed differences in grain yield. Out of the two main yield components, grain number per plant was affected by allelic variants at Rht-B1 and Ppd-A1 loci, while no differences were observed in thousand kernel weight. The increases in grain number per spike associated with Rht-B1b were attributed to a higher grain number per spikelet, whereas Ppd-A1a (GS105) was associated with higher grain number per spikelet, but also with lower spikelets per spike.